Processes of Glocalization in Development of Modern Territory - Miszczak, Katarzyna (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
Globalization and its indigenization – glocalization are contemporary determinants of processes of social and economic development of particular states and societies. "Think globally, act locally" is currently keynote in management of innovative space. The main aim of this article is attempt of defining and short characteristic of problems of globalization and glocalization as regards some aspects of development of modern territory. As a reason of the elaboration's limited volume presented matters, opinions and conclusions were depicted in synthetic form.